Globalization and apprenticeships: Does apprenticeship survive in transnational companies? - Gonon, Philipp [Verfasser]; Hippach-Schneider, Ute [Verfasser]; Weigel, Tanja [Verfasser] (My University, 2011)
"The following paper is focused on recruiting policies of transnational companies (TNCs) and the required competencies, asking if youngsters with an apprenticeship background are seen as being still able to fulfill tasks in a knowledge-based economy. The TNCs rely more and more on academic knowledge for work, sometimes formerly done by skilled workers. Most of our interviewed recruiters of 18 TNCs, based in Germany, England and Switzerland know the advantages of apprenticeships, especially if they have a tradition in dual model countries like Germany and Switzerland. We argue that a modernized apprenticeship which takes academic knowledge more into account, languages (especially English), entrepreneurship and 'soft skills', which is permeable to other learning opportunities as a basis for further education has a good prospect in the near future." (Autorenreferat, BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; G 2.1 Globalisierung; S 5.3 Personalentwicklung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Multinationales Unternehmen; Qualifikationsbedarf; Personalgewinnung; Ausbildungsabschluss; Bachelor; Mittlere Qualifikation; Internationaler Vergleich; Bundesrepublik Deutschland; England; Schweiz